Using microbiome information to understand and improve animal performance - Jeferson Menezes Lourenco; Christina Breanne Welch (Italian Journal of Animal Science, 2022)
For many years, microbiology was based on culture-dependent methods to study microorganisms; however, the latest technologies are culture-independent and their development has generated large amounts of new data, allowing researchers to understand the true nature and complexity of animals’ microbiomes. The myriad of microorganisms living in a symbiotic relationship with animals, primarily in their gastrointestinal tract (GIT), interact with the host animal in many different ways, ultimately affecting the animal’s health and productivity. The purpose of this article is to address the use of microbiome information through the lens of animal science. It covers some best practices for performing microbiome studies, from proper sample collection to useful data analysis tools and packages. It also provides examples of how the microbiome can interact with the host to impact its health and productivity. Lastly, we present some future perspectives for animal microbiome research and how the information generated can be utilised for more accurate comparison across studies and integrated with other branches of the animal sciences so the data produced can have a larger, more beneficial impact.Highlights DNA sequencing costs have sharply dropped in the last two decades, enabling more accessibility for studies to utilise nucleotide sequencing technologies to investigate microbiomes. There is increasing evidence that the microorganisms living on, and especially inside a host animal, can affect animal health and performance-related traits. This review addresses utilising microbiome information in Animal Science and suggests some best practices for performing microbiome studies, which spans from sample collection to data analysis.